Taxing Immovable Property Revenue Potential and Implementation Challenges - Norregaard, John (IMF Working Papers; Working Paper ;, 2013)
The tax on immovable property has been characterized as probably the most unpopular among tax instruments, in part because it is salient and hard to avoid. But economists continue to emphasize the virtues of the property tax owing to its relatively low efficieny costs, benign impact on growth, and high score on fairness. It is, therefore, generally considered to be underutilized in most countries. This paper takes stock of the arguments for using real property taxation, and presents an updated data-set for high-and middle income countries to illustrate its use. It also reflects the renewed and widespread interest in property tax reform globally, and discusses the many policy and administrative issues that must be carefully considered as prerequisites for successful property tax reform.